Novel Comprehensive Molecular and Ecological Study Introducing Coastal Mud Shrimp (Solenocera Crassicornis) Recorded at the Gulf of Suez, Egypt - Eman M. Abbas; Fawzia S. Ali; Mohammed G. Desouky; Mohamed Ashour; Ahmed El-Shafei; Mahmoud M. Maaty; Zaki Z. Sharawy (Journal of Marine Science and Engineering, 2020)
Solenocera crassicornis is a commercially important shrimp of the Solenoceridae family. The current study investigated the morphology, molecular identification, phylogenetic relationships, and population dynamics of S. crassicornis in Egypt. Samples were collected monthly (total, 1722; male = 40.19%, wet weight, 0.89–10.77 g; female = 59.81%, wet weight, 1.55–19.24 g) from Al-Attaka commercial catch in the Gulf of Suez in the Red Sea. Two barcode markers, 18S rRNA and cytochrome c oxidase subunit I (COI), were used for molecular identification. COI partial sequences were used to construct the phylogenetic relationships among different species of genus Solenocera and to infer the origin of the studied Solenocera crassicornis. The applied molecular markers successfully identified the studied species to the species level. The genetic distances among S. crassicornis sequences from different countries revealed the Indo-West Pacific origin of S. crassicornis. The relationship between total length (TL) and total weight (TW) was TW = 0.035TL2.275 and r2 = 0.805 for males and TW = 0.007TL3.036 and r2 = 0.883 for females, indicating that females were heavier than males. Despite its social and economic relevance in the area, information on the hatching, larval rearing, and farming of S. crassicornis is scarce and requires future studies under Egyptian conditions.